1999
DOI: 10.1346/ccmn.1999.0470303
|View full text |Cite
|
Sign up to set email alerts
|

Clay Diagenesis in the Sandstone Reservoir of the Ellon Field (Alwyn, North Sea)

Abstract: Abstract--The nature, composition, and relative abundance of clay minerals in the sandstones of the Brent Group reservoir were studied between 3200-3300 m in a well of the Ellon Field (Alwyn area, North Sea). The sandstones have a heterogeneous calcite cement which occurred during early-diagenesis. Clay diagenesis of the cemented and uncemented sandstones was investigated using optical microscopy, scanning electron microscopy (SEM), X ray diffraction analyses (XRD), and infrared spectroscopy (IR). The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…Kaolin and illite in sandstones kaolin evolution as a function of temperature or parameters such as porosity or timing of reservoir invasion by hydrocarbons (Ehrenberg et al, 1993;Macaulay et al, 1993;McAulay et al, 1993;Lanson et al, 1995Lanson et al, , 1996Beaufort et al, 1998;Cassagnabère, 1998;Cassagnabère et al, 1999;Hassouta, 1999;Hassouta et al, 1999). These studies have consistently shown that blocky dickite results from the diagenetic evolution of early vermiform kaolinite with increasing temperature rather than from a direct precipitation event induced by a late flush by meteoric fluids.…”
Section: Evidence For a Diagenetic Kaolinite-to-dickite Conversionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kaolin and illite in sandstones kaolin evolution as a function of temperature or parameters such as porosity or timing of reservoir invasion by hydrocarbons (Ehrenberg et al, 1993;Macaulay et al, 1993;McAulay et al, 1993;Lanson et al, 1995Lanson et al, , 1996Beaufort et al, 1998;Cassagnabère, 1998;Cassagnabère et al, 1999;Hassouta, 1999;Hassouta et al, 1999). These studies have consistently shown that blocky dickite results from the diagenetic evolution of early vermiform kaolinite with increasing temperature rather than from a direct precipitation event induced by a late flush by meteoric fluids.…”
Section: Evidence For a Diagenetic Kaolinite-to-dickite Conversionmentioning
confidence: 98%
“…This suggests that hydrocarbon invasion occurred as dickite crystallization was in progress and that mineral reactions feeding dickite precipitation were inhibited because of the reduced amount of pore water. In the Ellon Field (Alwyn, North Sea), Hassouta (1999) and Hassouta et al (1999) Beaufort et al, 1998;Cassagnabère, 1998).…”
Section: Evidence For a Diagenetic Kaolinite-to-dickite Conversionmentioning
confidence: 99%
“…These sandstones are also distinct from those in the main study area due to their high proportion of K1 relative to WM1. Considering that the replacement of early kaolinite by later white mica is typically a feature marking increasing temperatures during diagenesis (Lanson et al, 1996;Berger et al, 1997;Hassouta et al, 1999), it is probable that the Roraima Supergroup at Makari Mountain was not buried as deeply as it was in the main study area, and could have constituted a separate sub-basin with an abbreviated burial history.…”
Section: Early Diagenesismentioning
confidence: 99%
“…Nevertheless, based on their morphology, the kaolin crystals could be kaolinite. Indeed, cluster or vermiform kaolinite is the common form of diagenetic kaolin in sandstones (Hassouta, Buatier, Potdevin, & Liewig, 1999). Whatever the exact polytype, the precipitation of kaolin in open pores and the preservation of the aluminous detrital minerals both indicate an episode of an aluminous-rich fluid flow through the sandstones.…”
Section: Petrographic and Diagenetic Characteristicsmentioning
confidence: 99%